A risky investment? Examining the outcomes of emotional investment in Instagram. (December 2019) - Lowe-Calverley, Emily; Grieve, Rachel; Padgett, Christine
Highlights: First to operationalise Instagram Investment. Instagram Investment significantly predicts depression and stress. Instagram Investment does not significantly predict anxiety. Number of followers indirectly reduces self-esteem via Instagram Investment. Abstract: Recent research demonstrates links between aspects of Instagram use and negative psychological outcomes. It is therefore important to be able to predict the users who may be at a greater risk of experiencing negative consequences as a result of their use. Instagram is an immersive platform and peoples' behaviour on Instagram can be important to their self-concept and self-esteem; users are potentially deeply emotionally invested in their Instagram use. This paper presents three studies investigating an Instagram-specific form of emotional investment – Instagram Investment. Study 1 ( N  = 167) examined Instagram Investment as a predictor of depression, anxiety, and stress, within a series of hierarchical multiple regression models, and demonstrated the potential utility of Instagram Investment for the prediction of depression and stress. In Study 2 ( N  = 120) we expanded our understanding of Instagram Investment within the context of self-esteem. A mediation model revealed an indirect effect of number of followers on self-esteem via Instagram Investment. Finally, in Study 3 ( N  = 259) we examined the structural properties of the 6 items used to measure Instagram Investment using a confirmatory factor analysis. Together, these studies demonstrate that Instagram Investment is a new and valuable construct for explaining the way that individuals are impacted by their use of Instagram.